Jean-Francois Lyotard - Malpas, Simon (Routledge, 2003)
Jean-Francois Lyotard is one of the most celebrated proponents of what has become known as the 'postmodern'. More than almost any other contemporary theorist, he has explored the relations between knowledge, art, politics and history, in ways that offer radical new possibilities for thinking about modern culture. Simon Malpas introduces students to issues at the heart of Lyotard's work, including *modernity and the postmodern *the sublime *ethics *history and representation *art and the unpresentable *knowledge, the university and the future. Lyotard's work is impossible to dismiss or ignore for anybody who is serious about contemporary literature and culture, and this guide provides the ideal companion to the wide variety of his critical texts.